Nitrile-Containing Fischerindoles from the Cultured Cyanobacterium Fischerella sp - Kim, Hyunjung (2012)
Chemical investigation of the cultured cyanobacterium Fischerella sp. (SAG strain number 46.79) led to the isolation of four nitrile-containing indole alkaloids, namely 12-epi-fischerindole I nitrile (1), deschloro 12-epi-fischerindole I nitrile (2), 12-epi-fischerindole W nitrile (3), and deschloro 12-epi-fischerindole W nitrile (4) along with a known metabolite hapalosin. The structures were determined by detailed spectroscopic analyses on the basis of 1D and 2D NMR and HRESIMS data. All isolates were evaluated for cytotoxicity against human cancer cells and for 20S proteasome inhibition. Deschloro 12-epi-fischerindole I nitrile (2) was found to be weakly cytotoxic against HT-29 cells with an ED(50) value of 23 μM. Hapalosin showed weak cytotoxicity against HT-29 and MCF-7 cells with ED(50) values of 22 and 27 μM, respectively, as well as moderate 20S proteasome inhibition with an IC(50) value of 12 μM. Compounds 1-4 all contain a nitrile moiety instead of the isonitrile found in all fischerindoles reported to date. Compounds 3 and 4 also display a new carbon skeleton, in which a six-membered ring replaces the five-membered ring normally found in fischerindole-type alkaloids.